Does scientific forest management promote plant species diversity and regeneration in Sal (Shorea robusta) forest? A case study from Lumbini collaborative forest, Rupandehi, Nepal - Awasthi, N.; Bhandari, S. K.; Khanal, Y. (Banko Janakari, 2015)
Scientific forest management is an emerging need for managing existing natural forests of Nepal on the basis of silvicultural intervention. The study was carried out in Lumbini Collaborative Forest at Rupandehi District of Nepal, where Sal (Shorea robusta) forests are being managed under Irregular Shelterwood System with eighty years of cutting cycle since 2011–2012. The study was purposed to find out the intial effects of silvicultural intervention on plant species diversity and regeneration of Sal forest. The vegetative sampling was done using quadrate method based on the principle of simple random sampling both in the managed as well as the unmanaged parts of forest. The study found out remarkable increase in regeneration as well as decrease in plant diversity in the managed first and second-year stands (Block I and Block II respectively) as compared to the unmanaged stand (Block III) at its initial level of implementation. The mean value of diversity, richness, evenness, dominance index and regeneration of S. robusta varied significantly (p?0.05) between the managed blocks (stands). The seedling density of S. robusta was found higher in the managed blocks (Block I and Block II) as compared to the unmanaged one (Block III) in terms of height class. The study recommends implementation of Irregular Shelterwood System for managing the existing degraded Sal forests of the Terai region of Nepal, however, its long term effects on plant species diversity should be further studied in detail. Banko Janakari, A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page: 20-29